TAYANGAN INFOTAINMENT MENGKONSTRUKSI ESKAPISME BUDAYA - Agus Maladi Irianto (Universitas Diponegoro, 2013)
ABSTRACT The infotainment show becomes one of reliable shows for several national private TV in Indonesia. The following article is discussing about the presence of the show program that dominated the duration of TV stations in Indonesia. It is used as an effective media by the society members (TV viewers) to conduct cultural escapism. Infotainment show is becoming one of the gossip industries in Indonesia that is used as a medicine for society members to escape from the daily reality. Keywords: Infotainment Show, cultural escapism, and gossip industry